The Role of Knowledge Management Elements in the Improvement of the Faculty Members in Distance Education Universities) designing an appropriate model - Mozaffar Sharifzadeh; Sana Safari (Zanjan University of Medical Sciences and Health Services, 2019)
Background and Objective: Given the importance and status of faculty members in universities, the advancement of the duties and missions of the higher education system and rapid development of the technologies and challenges faced by educational institutions require proper measures for the continuous development and overall improvement of these systems, especially the improvement of the capacities, scientific capabilities, and professional skills of faculty members through knowledge management. The present study aimed to assess the role of the elements of knowledge management in the improvement of the faculty members in distance education universities by designing an appropriate model. Materials and Methods: This applied, qualitative research was conducted on the faculty members of distance education research universities in Iran, including 5,101 faculty members. The participants were selected via stratified random sampling (n=357) and based on Morgan's table. Data were collected using a questionnaire. The validity of the research instrument was confirmed by experts, and its reliability was confirmed using the Cronbach's alpha, which was estimated at 0.89 for knowledge management and 0.91 for knowledge development items. Data analysis was performed in SPSS using the Kolmogorov-Smirnov test for data normalization. In addition, the path and fitting of the model were examined using structural equations in AMOS software. Results: In this research, knowledge management indicators (creation, sharing, storage, and application of knowledge) affected all the improvement indicators (individual, professional, and organizational), so that the overall effect of knowledge management on improvement was estimated at 69.3 in the model fitting index table. Conclusion: According to the results, knowledge management is a conscious strategy for creating, sharing, storing, and applying knowledge, thereby enhancing the performance of the faculty members in distance education universities and enabling them to become an efficient element of change in universities.